Financial adulting : everything you need to know and do to be a financially confident and conscious adult - Gerstley, Ashley Feinstein (Wiley, 2022)
"Financial Adulting is an easy-to-follow, informative, and fun financial guide. The book covers everything you need to know and do to be a confident and competent financial adult. It includes all the personal finance education most of us were missing, but also the accompanying tactical step-by-step guidance so readers can take action and create systems to set themselves up for success months and years after they read the book. Gerstley shares everything readers need to know about budgeting, building their rainy day fund, retirement investing, understanding insurance, filing taxes, increasing their credit score, making a plan for student loans, and everything in between. Personal finance is also very personal. We all value different things and therefore our money lives will all look unique. Readers will not have to give up their lifestyles or what they love most. They can live big meaningful lives now while also reaching their financial goals. Full of practical advice, Financial Adulting will be a resource that readers will first read cover to cover and then come back to again and again when it's time to adjust their 401(k)s, when they are preparing for a salary negotiation, or are mapping out how to save for a new goal. Gerstley shares all of this from an important racial justice and feminist perspective, as we can't talk about money and personal finance without talking about equity. Financial adults understand this important context and recognize that they may be coming from a place of disadvantage due to historic and systemic obstacles. Financial adults also recognize that their privilege can and should be used to help close racial and gender wealth gaps. The book provides readers with everything they need to become confident and competent financial adults and start building meaningful wealth, one small manageable step at a time."--